Embodied cognition and curriculum construction - Wang, Mei-qian; Zheng, Xu-dong (Educational philosophy and theory, 2018)
The disembodiment of cognitive science has resulted in curricula with disembodied concepts and practice. The emergence of the embodied cognitive science provoked public reflections on the nature of the curriculum. This has elevated the body from the 'peripheral' position to the 'central' position, acting as the subject in action and becoming the bridge to experience transformations. Meanwhile, the nurturing role of the environment for the mind is attracting increasingly more attention, and the environment, the body, and the mind jointly constitute a dynamic system that prompts the transformation and restructuring of learners' experience. The reshaping of the relationship between the body and education and the integration of physical experience and mind-building have led us to examine curriculum from a completely new perspective, and curriculum construction is thus transformed to the dynamic generation of interaction among the body, the mind, and the environment based on group experiences. To be precise, there are three basic dimensions in the construction of an embodied curriculum: (1) returning to the life-world and promoting the integration of the curriculum narrative framework and the student's learning trajectory; (2) introducing the embodied experience and realizing the continuous interactions among the learner's body, mind, and environment; and (3) integrating the functions of technologies to provide a powerful mediating tool for the construction of embodied curriculum.